The Influence of corporate governance, audit quality, and ownership, on financial instrument disclosure in Indonesia - Probohudono, Agung Nur; Sugiharto, Bambang; Arifah, Siti (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
This research analyzed the influence of corporate governance, audit quality, public ownership, and foreign ownership, on financial instrument disclosure by Indonesian firms. Leverage, ROA, and size were used as control variables. The sample comprised of 71 manufacturing firms, determined using a purposive sampling method. Observational data for the years 2009-2013, are in the transition period of International Financial Reporting Standards implementation. Analyze data using multiple regressions. Test results show simultaneously, the scores of independent and control variable have positive influence. The results of partial testing of corporate governance, audit quality, public ownership, and foreign ownership scores have significantly positive influence.